A potential association of RNF219‐AS1 with ADHD: Evidence from categorical analysis of clinical phenotypes and from quantitative exploration of executive function and white matter microstructure endophenotypes. (28th February 2021) - Fu, Guang‐Hui; Chen, Wai; Li, Hai‐Mei; Wang, Yu‐Feng; Liu, Lu; Qian, Qiu‐Jin
Abstract: Aims: Attention‐deficit/hyperactivity disorder (ADHD) is a neuropsychiatric disorder of substantial heritability, yet emerging evidence suggests that key risk variants might reside in the noncoding regions of the genome. Our study explored the association of lncRNAs (long noncoding RNAs) with ADHD as represented at three different phenotypic levels guided by the Research Domain Criteria (RDoC) framework: (i) ADHD caseness and symptom dimension, (ii) executive functions as functional endophenotype, and (iii) potential genetic influence on white matter architecture as brain structural endophenotype. Methods: Genotype data of 107 tag single nucleotide polymorphisms (SNP) from 10 candidate lncRNAs were analyzed in 1040 children with ADHD and 630 controls of Chinese Han descent. Executive functions including inhibition and set‐shifting were assessed by STROOP and trail making tests, respectively. Imaging genetic analyses were performed in a subgroup of 33 children with ADHD and 55 controls using fractional anisotropy (FA). Results: One SNP rs3908461 polymorphism in RNF219 ‐ AS1 was found to be significantly associated with ADHD caseness: with C‐allele detected as the risk genotype in the allelic model ( P = 8.607E‐05) and dominant genotypic model ( P = 9.628E‐05). Nominal genotypic effects on inhibition ( p = 0.020) and set‐shifting ( p = 0.046) were detected. While no direct effect on ADHD core symptoms was detected, mediation analysis suggested that SNP rs3908461 potentially exerted an indirect effect through inhibition function [B = 0.21 (SE = 0.12), 95% CI = 0.02‐0.49]. Imaging genetic analyses detected significant associations between rs3908461 genotypes and FA values in corpus callosum, left superior longitudinal fasciculus, left posterior limb of internal capsule, left posterior thalamic radiate (include optic radiation), and the left anterior corona radiate ( P FWE corrected < 0.05). Conclusion: Our present study examined the potential roles of lncRNA in genetic etiological of ADHD and provided preliminary evidence in support of the potential RNF219 ‐ AS1 involvement in the pathophysiology of ADHD in line with the RDoC framework. Abstract : A key noncoding RNA variant was found to be associated with the risk of ADHD children in Chinese Han, and the mechanism of this variant affected symptom performance was through the indirect effect of inhibition control. This important DNA polymorphism locus in lncRNA could affect white matter microstructure by the imaging genetic analyses.